Antibodies targeting the interleukin-5 signaling pathway used as add-on therapy for patients with severe eosinophilic asthma: a review of the mechanism of action, efficacy, and safety of the subcutaneously administered agents, mepolizumab and benralizumab. (2nd April 2020) - Hillas, Georgios; Fouka, Evangelia; Papaioannou, Andriana I
ABSTRACT: Introduction : Since the discovery of eosinophils in the sputum of asthmatic patients, several studies have offered evidence on their prominent role in the pathology and severity of asthma. Blood eosinophils, are a useful biomarker for therapy selection in severe asthma patients. IL-5 plays crucial role on maturation, activation, recruitment, and survival of eosinophils and constitutes an important therapeutic target for patients with severe uncontrolled eosinophilic asthma. Areas covered : This review focuses on the similarities and differences on mechanisms of action, efficacy, and safety, of two subcutaneously(SC) administered agents, the anti-interleukin(IL)-5 monoclonal antibody mepolizumab and the IL-5 receptor-α(IL-5Rα)-directed cytolytic monoclonal antibody benralizumab. All information used was collected from PubMed using keywords such as severe asthma, eosinophils, IL-5, airway inflammation, asthma exacerbations, mepolizumab, benralizumab, anti-IL5, and anti-IL5R either as single terms or in several combinations. Expert opinion : Both mepolizumab and benralizumab are promising for the treatment of severe eosinophilic asthma resulting in asthma control improvement and exacerbations reduction and can serve as steroid-sparing agents. However, since no head-to-head comparisons exist, it is unknown whether their different mechanisms of action might be related to different efficacy in specific patients' sub-phenotypes. Long-term clinical observations will provide real-world evidence regarding their lasting effectiveness and safety.